Storage Resistance and Volatile Matter Changes in Two Varieties of Raspberries - Chao GE; Peng ZHANG; Jiangkuo LI; Xiaoyu JIA; Di WU; Chunyuan LI; Ling LIU (Shipin gongye ke-ji)
To compare the storage tolerance and volatiles of 'Haritaz' and 'Nova' raspberries, used these varieties as test materials. After harvesting, the raspberries were stored in air-conditioned boxes at 0 ℃. The sensory scores and nutritional indexes of both varieties were determined and the changes in volatile substances were analyzed using GC-IMS and GC-MS techniques. At 15 d of storage, the sensory score, good fruit rate, solid-acid ratio, and vitamin C content of 'Nova' raspberries were significantly higher than those of 'Haritaz' raspberries (P<0.05). 'Haritaz' raspberries exhibited a slight mold growth phenomenon. The GC-IMS results indicated that esters constituted a higher proportion of volatile substances in raspberries, with methyl acetate and ethyl acetate being the primary ones. The concentration of volatile substances in 'Haritaz' raspberries decreased with storage time, while that in 'Nova' raspberries increased, with a significant difference at 15 d. The identification of the two raspberry varieties was possible based on their volatile substances. The GC-MS results indicated that terpenoids were present in high relative content in raspberries. Beta-violetone was identified as the main volatile substance common to both raspberry varieties, while alpha-violetone was unique to 'Nova' raspberries. Alpha-violetone had antioxidant, anti-inflammatory and antibacterial effects. The relative content of alcohols in 'Haritaz' raspberries increased significantly with storage time (P<0.05), while the relative content of terpenes and esters decreased significantly, resulting in flavor loss. In contrast, the proportion of volatiles in 'Nova' raspberries remained stable, maintaining their flavour. Therefore, in terms of storability and retention of volatiles, 'Nova' raspberries were superior to 'Haritaz' raspberries.